平面3-DOF混联机构构型综合及其同构分析 - 吴凡; 李瑞琴 (Jixie chuandong)
Through the application of Assur bar groups method and graph theory,the link classification and link composition are finished to get the most basic kinematic chain’s structure of the planar 3-DOF mechanism with full revolute pairs which has three symmetrical branched chains.Then topological embryonic graph is drawn using the interpolation point method of the topological embryonic graph.The classification of the branched chains is done and the chains are inserted in the topology embryonic graph.Through the isomorphism analysis,the 6 configurations of kinematic chains are obtained.Finally,using a new graph theory description method based on the link’s relationship the hybrid configuration of planar 3-DOF is obtained,then the application research is proceeded.Doing these can lay the foundation for the study of the planar 3-DOF mechanism with non full revolute pairs.At the same time,the study of the planar 3-DOF mechanism is also more conducive to the research of the spatial lower-freedom mechanism.